EFFECTIVE MANAGEMENT OF PROFESSIONAL TRAINING FOR ELECTRICAL ENGINEERS: CURRENT CHALLENGES AND FUTURE PROSPECTS - Pecheniuk, Andrii; Dumanskyi, Oleksandr; Vyshynska, Olha; Vyshynskyi, Oleksandr (Public Management and Policy, 2025)
The article explores current challenges and outlines promising directions for the development of professional competencies among students in the field of electrical engineering in response to modern demands in the energy sector. The purpose of the study is to analyze current issues in the development of professional competencies among students in the field of electrical engineering, as well as to develop promising areas for improving the professional training system. The study uses a theoretical and analytical approach to examine the problems and prospects of developing professional competencies of students in electrical engineering through the analysis of scientific publications, educational standards, regulatory documents, comparison of market requirements with the competency characteristics of programs, generalization of typical problems and prospects, as well as research into dual education practices, digitalization, STEM approaches, and stakeholder engagement, using sources from Ukrainian scientists, industry publications, and resources from organizations and employers as an information base. The study analyzes current labor market requirements for electrical engineers, with a particular focus on the competency-based approach as a foundation for professional training. Key barriers to the formation of professional competencies are identified, including insufficient practical training, outdated educational programs, limited collaboration with employers, and low student motivation. The paper highlights prospective areas for improving training systems, such as the implementation of dual education, the renewal of educational content, enhancement of institutional infrastructure, professional development of teaching staff, and the integration of digital technologies and STEM-based approaches. Special attention is given to the role of stakeholders in the competency formation process, particularly the importance of partnerships with industry, as well as the involvement of graduates, employers, and professional communities. The findings of this study may be valuable for researchers, educators, administrators, and all stakeholders interested in modernizing professional education in the field of electrical engineering.